Design and realization of a randomized modulation scheme for digital class D amplifiers - Cheng, Kuan Teng. (2013)
Digital Class D amplifiers are increasingly prevalent in portable audio electronic devices because of their high power-efficiency and simple hardware advantages. Digital Class D amplifiers typically modulate the output signal using the Pulse Width Modulation Scheme (PWM). The PWM, unfortunately, generates undesirable harmonics of the input signal that cause distortion in the output signal.